Immunization with 60 kD Ro peptide produces different stages of preclinical autoimmunity in a Sjögren's syndrome model among multiple strains of inbred mice. (6th June 2013) - Kurien, B. T.; Dsouza, A.; Igoe, A.; Lee, Y. J.; Maier‐Moore, J. S.; Gordon, T.; Jackson, M.; Scofield, R. H.
Summary Sjögren's syndrome is a chronic illness manifested characteristically by immune injury to the salivary and lacrimal glands, resulting in dry mouth/eyes. Anti‐Ro [Sjögren's syndrome antigen A (SSA)] and anti‐La [Sjögren's syndrome antigen B (SSB)] autoantibodies are found frequently in Sjögren's subjects as well as in individuals who will go on to develop the disease. Immunization of BALB/c mice with Ro60 peptides results in epitope spreading with anti‐Ro and anti‐La along with lymphocyte infiltration of salivary glands similar to human Sjögren's. In addition, these animals have poor salivary function/low saliva volume. In this study, we examined whether Ro‐peptide immunization produces a Sjögren's‐like illness in other strains of mice. BALB/c, DBA‐2, PL/J, SJL/J and C57BL/6 mice were immunized with Ro60 peptide‐274. Sera from these mice were studied by immunoblot and enzyme‐linked immunosorbent assay for autoantibodies. Timed salivary flow was determined after pharmacological stimulation, and salivary glands were examined pathologically. We found that SJL/J mice had no immune response to the peptide from Ro60, while C57BL/6 mice produced antibodies that bound the peptide but had no epitope spreading. PL/J mice had epitope spreading to other structures of Ro60 as well as to La, but like C57BL/6 and SJL/J had no salivary gland lymphocytic infiltration and no decrement of salivary function. DBA‐2 and BALB/c mice had infiltration but only BALB/c had decreased salivary function. The immunological processes leading to a Sjögren's‐like illness after Ro‐peptide immunization were interrupted in a stepwise fashion in these differing mice strains. These data suggest that this is a model of preclinical disease with genetic control for epitope spreading, lymphocytic infiltration and glandular dysfunction.